Family adjustment to diabetes diagnosis in children: Can participation in a study on type 1 diabetes genetic risk be helpful?. Issue 5 (2nd May 2018) - Smith, Laura B; Liu, Xiang; Johnson, Suzanne Bennett; Tamura, Roy; Elding Larsson, Helena; Ahmed, Simi; Veijola, Riitta; Haller, Michael J; Akolkar, Beena; Hagopian, William A; Rewers, Marian J; Krischer, Jeffrey; et al.
Abstract : Background: Diagnosis of type 1 diabetes often causes a negative psychological impact on families. We examined whether parents and children enrolled in The Environmental Determinants of Diabetes in the Young (TEDDY) study differ in their psychological adjustment to diabetes diagnosis compared to children diagnosed with diabetes in the community. Methods: TEDDY follows 8676 children at genetic risk for type 1 diabetes from birth. Fifty‐four TEDDY children diagnosed with diabetes and 54 age‐matched community control children diagnosed with diabetes were enrolled. Participants were aged 3 to 10 years and study visits occurred at 3, 6, and 12 months postdiagnosis. Psychological measures included an adapted diabetes‐specific State Anxiety Inventory, the Pediatric Quality of Life Inventory—Diabetes Module, and the Pediatric Inventory for Parents, which measures frequency and difficulty of parenting stress. Results: A generalized estimating equation analysis based on a difference score between TEDDY children and community controls found no significant differences between TEDDY parents and community controls on parent diabetes‐specific anxiety ( P  = .30). However, TEDDY children exhibited better diabetes‐specific quality of life ( P  = .03) and TEDDY parents reported lower frequency ( P  = .004) and difficulty ( P  = .008) of parenting stress compared to community controls. Conclusions: Children diagnosed with at‐risk for type 1 diabetes who have previously enrolled in research monitoring have improved diabetes quality of life and lower parenting stress postdiagnosis compared to children diagnosed in the community. Families in follow‐up studies may be more prepared if their child is diagnosed with diabetes.